Feeding studies on abalone Haliotis asinina (Linne) early juveniles using five benthic diatom strains - Franco, Annie U. Villa (Miagao, Iloilo University of the Philippines Visayas, 2014)
This study assessed the feeding activities of 3 and 5 mm sized H. asinina early juveniles using five specific diatom strains namely Navicula ramossisima, Amphora sp., Cocconeis sp., and Diploneis sp. Results showed that the feeding activity of abalone early juveniles H. asinina is "not strictly" nocturnal but lower feeding activity was observed at 10 am - 2pm (p<0.05). When diatoms are offered, the juveniles would graze upon them, however their grazing capability depends on the attachment, size, and frustule strength of the diatom. Lesser preference of juveniles for Diploneis sp. was observed compared to the other diatom strains. , Juveniles fed Amphora sp., N. ramossisima and Nitzschia sp. showed higher growth rates in shell length and body weight (SGR = 1.85 - 1.99 percent SL d-1, 2.2 - 2.8 percent BW d-1) in both sizes. Survival rates (46-71 percent) was not significantly different among Amphora sp., N. ramossisima, Nitzschia sp. and Cocconeis sp., but significantly higher than Diploneis sp. (8-12 percent) (p<0.05). The results strongly indicate that Amphora sp. and Nitzschia sp. are live food for early juveniles and could substitute for N. ramossisima in abalone hatcheries. On the contrary, Diploneis sp. induced poor survival rates in both sizes of early juveniles and is hereby not recommended as feed for abalone hatcheries. The identified potential diatom strains (Amphora sp., Nitzschia sp. and N. ramossisima) can improve feeding efficiency of abalone juveniles, thereby address the problems of large scale production in abalone hatcheries in the Philippines.
Thesis (M.S. Biology)-- Miagao, Iloilo : University of the Philippines Visayas, May 2014.
Keywords: Feeds and feedings -- H. asinina; Benthic diatom strains